2010
DOI: 10.2193/2009-266
|View full text |Cite
|
Sign up to set email alerts
|

Novel Scavenger Removal Trials Increase Wind Turbine—Caused Avian Fatality Estimates

Abstract: For comparing impacts of bird and bat collisions with wind turbines, investigators estimate fatalities/megawatt (MW) of rated capacity/year, based on periodic carcass searches and trials used to estimate carcasses not found due to scavenger removal and searcher error. However, scavenger trials typically place ≥10 carcasses at once within small areas already supplying scavengers with carcasses deposited by wind turbines, so scavengers may be unable to process and remove all placed carcasses. To avoid scavenger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 4 publications
4
97
0
Order By: Relevance
“…For example, Erickson et al (2000) reported an average survival time of 25.0 days in Oregon, whereas Smallwood et al (2010) reported 4.45 days in California. Villegas-Patraca et al (2012) reported similar results in Mexico to those of Smallwood et al (2010).…”
Section: Scavenger Removal Across Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, Erickson et al (2000) reported an average survival time of 25.0 days in Oregon, whereas Smallwood et al (2010) reported 4.45 days in California. Villegas-Patraca et al (2012) reported similar results in Mexico to those of Smallwood et al (2010).…”
Section: Scavenger Removal Across Studiesmentioning
confidence: 99%
“…For example, Erickson et al (2000) reported an average survival time of 25.0 days in Oregon, whereas Smallwood et al (2010) reported 4.45 days in California. Villegas-Patraca et al (2012) reported similar results in Mexico to those of Smallwood et al (2010). Each of these studies had larger average survival times than our study, which suggests that the results from wind turbine studies are not accurate for use in estimates of urban bird-window collision fatalities.…”
Section: Scavenger Removal Across Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Several factors could lead to overestimates of searcher efficiency, including use of inappropriate carcasses that may be more conspicuous or larger than species that would be expected to be found during carcass searches (Labrosse 2008), concentrating carcasses in more exposed habitats within the search area, and failing to ensure that searcher efficiency trials occur without the knowledge of the observer. Scavenger rates may be biased if carcasses used in the trials are not fresh (Smallwood 2013), are not representative of the species being detected, or if too many carcasses are used at one time for trials, i.e., scavenger swamping (Smallwood et al 2010). All of these could result in underestimates of mortality.…”
Section: Collision Mortality Estimatesmentioning
confidence: 99%